Cities and metaphors beyond imaginaries of Islamic urban space - Falahat, Somaiyeh (Routledge, Taylor & Francis Group, 2018)
In the context of Islamic city studies, relying on reasoning and rational thinking has reduced descriptive, vivid features of the urban space into a generic scientific framework. Phenomenological characteristics have consequently been ignored rather than integrated into theoretical components. The book argues that this results from a lack of appropriate conceptual vocabulary in our global body of scholarly literature. It challenges existing theories, introduces and applies the urban concept of Hezar-tu to rethink the spaces of Fez, Isfahan and Tunis. This tool inverts the principles of conceptualising urban space and constructs a staging-post towards a different articulation based on in-between spaces rather than nodes, a logic of ambiguity rather than determinacy, and interior rather than exterior thinking.?
Description based on print version record
Keywords: Islamic cities and towns; Public spaces / Islamic countries; Architecture / Islamic countries; Urbanization / Islamic countries; City planning / Islamic countries